Star-spot activity, orbital obliquity, transmission spectrum, physical properties, and transit time variations of the HATS-2 planetary system - Biagiotti, Francesco; Mancini, Luigi; Southworth, J.; Tregloan-Reed, J.; Naponiello, L.; Jørgensen, U. G.; Bach-Møller, N.; Basilicata, M.; Bonavita, M.; Bozza, V.; Burgdorf, M. J.; Dominik, M.; et al. (Astronomy and astrophysics, 2024)
Aims. Our aim in this paper is to refine the orbital and physical parameters of the HATS-2 planetary system and study transit timing variations and atmospheric composition thanks to transit observations that span more than 10 yr and that were collected using different instruments and pass-band filters. We also investigate the orbital alignment of the system by studying the anomalies in the transit light curves induced by starspots on the photosphere of the parent star.
Gesehen am 07.04.2025